The multi‐faceted role of allergen exposure to the local airway mucosa. Issue 2 (13th December 2012) - Golebski, K.; Röschmann, K. I. L.; Toppila‐Salmi, S.; Hammad, H.; Lambrecht, B. N.; Renkonen, R.; Fokkens, W. J.; van, C. M.
Abstract Airway epithelial cells are the first to encounter aeroallergens and therefore have recently become an interesting target of many studies investigating their involvement in the modulation of allergic inflammatory responses. Disruption of a passive structural barrier composed of epithelial cells by intrinsic proteolytic activity of allergens may facilitate allergen penetration into local tissues and additionally affect chronic and ongoing inflammatory processes in respiratory tissues. Furthermore, the ability of rhinoviruses to disrupt and interfere with epithelial tight junctions may alter the barrier integrity and enable a passive passage of inhaled allergens through the airway epithelium. On the other hand, epithelial cells are no longer considered to act only as a physical barrier toward inhaled allergens, but also to actively contribute to airway inflammation by detecting and responding to environmental factors. Epithelial cells can produce mediators, which may affect the recruitment and activation of more specialized immune cells to the local tissue and also create a microenvironment in which these activated immune cells may function and propagate the inflammatory processes. This review presents the dual role of epithelium acting as a passive and active barrier when encountering an inhaled allergen and how this double role contributes to the start of local immune responses.